Genetic variations and alternative splicing: the Glioma associated oncogene 1, GLI1 - Zaphiropoulos, Peter (Frontiers in Genetics, 2012)
Alternative splicing is a post-transcriptional regulatory process that is attaining stronger recognition as a modulator of gene expression. Alternative splicing occurs when the primary RNA transcript is differentially processed into more than one mature RNAs. This is the result of a variable definition/inclusion of the exons, the sequences that are excised from the primary RNA to form the mature RNAs. Consequently, RNA expression can generate a collection of differentially spliced RNAs, which may distinctly influence subsequent biological events, such as protein synthesis or other biomolecular interactions. Still the mechanisms that control exon definition and exon inclusion are not fully clarified. This mini-review highlights advances in this field as well as the impact of single nucleotide polymorphisms in affecting splicing decisions. The Glioma associated oncogene 1, GLI1, is taken as an example in addressing the role of nucleotide substitutions for splicing regulation.